Aplicação de diferentes métodos para detecção de eventos adversos a medicamentos em uma unidade de terapia intensiva brasileira - Martins, Renato Rocha (2016)
Adverse drug events are damage caused by drugs. Their detection is important to identify risks that affect health system users and to design strategies that improve quality on healthcare. This study aimed to apply different methods of adverse drug event detection in patients admitted to intensive care unit of a public tertiary hospital in the Brazilian Midwest from September 2015 to April 2016. This study was approved by Hospital Alberto Rassi Ethics Committee on Research by report number 1,177,803 and the patients were invited to join voluntarily by signing the Informed Consent Form. In order to achieve the above objectives, this research was conducted in two phases. In the first phase, an analytical, retrospective study compared the use of trigger tool and a non-targeted chart review regarding to adverse drug event detection during hospitalization. Identified events were analyzed by multiprofessional team and classified as their causality, predictability, severity and damage level. In the second phase, this is an analytic, interventional study with purpose of evaluate the impact of medication therapy management on detection of drug-related problems and prevention of adverse drug events. Results found in two phases of this study allowed to recognize that all these tested methods were suitable for the purpose. The search for adverse events performed by trigger tool and a non-targeted chart review allowed identification of similar amounts of events, type of event and related drugs. In both groups the most frequently encountered events were related to metabolic, gastrointestinal, cardiovascular and hematological systems. In this phase, trigger tool application showed to be, among the strategies evaluated, the most convenient. The similar performance to non-targeted chart review supports the use of trigger tool in intensive care units routine, since this method requires less time to retrieve information from medical records. However, the possibility of early identifying a drug-related problem, preventing it from reaching the patient, and the possibility of intervening in non-preventable events, reducing harm, confer an advantage on medication therapy management. The proposed clinical pharmaceutical service allowed the detection of 50 adverse drug events, a low frequency compared to other methodologies. Although, this method was not considered inappropriate for the purpose, since it allowed identification and intervention in 170 other drug-related problems that had potential to cause patient damage. Problems identified at this phase were more often related antibacterials use, caused by improper drug combinations, inadequate dosing, and led to interventions that were accepted by the multiprofessional team, with more than 85% of adherence and total problem solving. These proposed detection methods allowed us to recognize characteristics of adverse drug events occurring in the institution. This information can be used later in order to outline strategies for improvement on healthcare quality. Inserting a clinical pharmacist into the multiprofessional team was a protective factor for critically ill patients, since this professional set up an additional barrier in order to detect and prevent adverse drug events, improving the safety on pharmacotherapy.